In the Footsteps of Amelia Brown: Collaborative Historical Ecology at Shin-yvslh-sri∼, a Tolowa Village on the North Coast of California. (2nd January 2020) - Tushingham, Shannon; Hopt, Justin; Christiansen, Colin; Bommelyn, Me'-lash-ne Loren; Green, John; Peterson, Michael R.; Steinruck, Suntayea; Stewart, Crista
Abstract: Research at Shin-yvslh-sri (CADNO-14), a pre-contact Tolowa village and shell midden site on the north coast of California, involves an innovative collaborative historical ecology approach—an explicitly multi-disciplinary cooperative effort between Tribal communities, a Federal agency, cultural resource management practitioners, and academic researchers. Multiple lines of evidence—including ethno-historic, oral history, and Traditional Ecological Knowledge (TEK) data, documentation of past archaeological research, analysis of varied scales of (micro and macro) archaeological data from both recent fieldwork and legacy collections—give a more complete picture of the historical ecology of the northern California coast. Results indicate that plank house village life emerged at Shin-yvslh-sri∼ approximately 1, 000 years ago, and that people pursued a wide array of marine and terrestrial taxa throughout its occupation. Archaeological data provide new evidence, as well as support for oral histories indicating the critical importance of mass captured smelt, as well as salmon, shellfish, and marine mammals. In addition to providing important data on coastal human-environmental systems, the project provides a case study model for future studies in collaborative historical ecology, particularly those that involve indigenous community concerns at endangered coastal archaeological and cultural sites.